A randomised controlled trial of ablation of Barrett's oesophagus with multipolar electrocoagulation versus argon plasma coagulation in combination with acid suppression: long term results. Issue 9 (11th August 2006) - Sharma, P; Wani, S; Weston, A P; Bansal, A; Hall, M; Mathur, S; Prasad, A; Sampliner, R E
Abstract : Background: Many modalities have been used to ablate Barrett's oesophagus (BO). However, long term results and comparative effectiveness are unknown. Aims: Our aim was to compare the long term efficacy of achieving complete reversal (endoscopic and histological) between multipolar electrocoagulation (MPEC) and argon plasma coagulation (APC) in BO patients and assess factors influencing successful ablation. Methods: Patients with BO, 2–6 cm long, underwent 24 hour pH testing on proton pump inhibitor (PPI) therapy. Patients were then randomised by BO length to undergo ablation with MPEC or APC every 4–8 weeks until endoscopic reversal or maximal of six treatment sessions. Results: Thirty five BO patients have been followed for at least two years following endoscopic ablation, 16 treated with MPEC and 19 with APC. There was complete reversal of BO in 24 patients (69%); 75% with MPEC and 63% with APC (p = 0.49). There was no difference in the number of sessions required in the two groups. There was no difference in age, pH results, BO length, PPI dose, or hiatal hernia size between patients with and without complete reversal. One patient developed an oesophageal stricture but there were no major complications such as bleeding or perforation. Conclusions: In BO patients treated with MPEC or APC in combination with acid suppression, at long term follow up, complete reversal of BO can be maintained in approximately 70% of patients, irrespective of the technique. There are no predictors associated with achieving complete reversal of BO. Continued surveillance is still indicated in the post ablative setting. As yet, these techniques are not ready for clinical application (other than for high grade dysplasia or early oesophageal adenocarcinoma) and cannot be offered outside the research arena.